2017
DOI: 10.4103/2249-4863.219994
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of foot care in patients with diabetes at central rural India

Abstract: Introduction:Diabetic foot syndrome is one of the common and most devastating preventable complications of diabetes mellitus (DM). It is associated with morbidity and premature mortality due to long-term complications affecting foot. The American Diabetes Association recommends that people with diabetes should have a comprehensive foot examination once per year. Most of the foot problems can be prevented with careful foot care. It may take effort and time to build up good foot care habits, but self-care is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 8 publications
4
32
1
2
Order By: Relevance
“…Out 14 who never walked bare foot only 5 developed foot ulcer but those who sometimes walked bare foot out of 209,116 developed foot ulcer. These results concur with those reported by Taksande, Thote, & Jajoo[16] in a study on attitude, practice, and knowledge on foot care among patients with diabetes at central rural India which showed that bare foot walking increases chance of developing foot ulcer.…”
supporting
confidence: 92%
“…Out 14 who never walked bare foot only 5 developed foot ulcer but those who sometimes walked bare foot out of 209,116 developed foot ulcer. These results concur with those reported by Taksande, Thote, & Jajoo[16] in a study on attitude, practice, and knowledge on foot care among patients with diabetes at central rural India which showed that bare foot walking increases chance of developing foot ulcer.…”
supporting
confidence: 92%
“…A study in central India in a similar rural training hospital reports that 63% of the patients have not undergone foot examination or received education regarding foot complications or foot care by their treating physicians. 21…”
Section: Discussionmentioning
confidence: 99%
“…Patients with poor knowledge and practices regarding diabetic foot care have a higher incidence of foot complications including ulcers. It may take effort and time to build up good foot care habits, but self-care is essential (Taksande, Thote & Jajoo, 2017).…”
Section: Introductionmentioning
confidence: 99%